A SrCO 3 / Polymer composite bone scaffold and preparation method thereof
Through the design and preparation of SrCO3/polymer composite bone scaffolds, the problem of degradation of polymer bone scaffolds in vivo to produce acidic products and lack of osteogenic activity is solved, and the effect of neutralizing acidic products and promoting osteogenic differentiation is achieved, and the effectiveness of bone defect repair is improved.
Patent Information
- Application Number
- CN202310888066.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing polymeric bone stents produce acidic products when degraded in the body, leading to inflammatory reactions and lacking osteogenic activity, which limits its application in the field of bone defect repair.
Using SrCO3/polymer composite bone scaffolds, a porous structural bone scaffold with a specific morphological structural size is prepared by compositeing SrCO3 microrods with polymer materials and selective laser sintering.
SrCO3 hydrolysis is alkaline, neutralizing the acidic products produced by the degradation of polymer materials in the bone scaffold, preventing inflammatory reactions, and promoting stem cells to differentiate into osteoblasts through the continuously released Sr ions, improving osteogenesis efficiency.
Smart Images

Figure CN116999614B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical technology, and specifically relates to a SrCO3 / polymer composite bone scaffold and a preparation method thereof. Background Art
[0002] Bone defect refers to the defect of bone tissue. It is a common orthopedic disease in clinical work. There are many patients with bone defects or functional disorders caused by traumatic fractures caused by traffic accidents or production safety accidents, bone tumors, bone tuberculosis and other orthopedic diseases. In addition, with the increase in the incidence of bone diseases in the elderly population, the number of patients with bone injuries is also increasing. Therefore, there is huge room for development in the repair and treatment of bone defects.
[0003] At present, the commonly used method for repairing large-area bone defects is to use autologous bone transplantation or allogeneic bone transplantation for treatment. Among them, autologous bone transplantation is the "gold standard" for bone defect repair because the transplanted bone tissue contains living cells, bioactive molecules, and blood supply. However, the amount of bone in the autologous bone donor area is limited, and it is often easy to cause complications of varying degrees due to increased operation time. Therefore, it is urgent to find suitable bone tissue engineering materials and prepare bone scaffolds.
[0004] Poly(lactic acid), poly(glycolic acid), poly(caprolactone) and other polymer materials are often selected to prepare bone scaffolds. Their advantages are that they have high mechanical strength and stiffness, and can mimic the load-bearing properties required for bone tissue regeneration. At the same time, the aforementioned polymer materials are also biocompatible and biodegradable, and their degradation products can be metabolized by the human body, eventually producing carbon dioxide and water, without causing toxic side effects to the human body. However, the aforementioned polymer materials will produce acidic products during the degradation process in the body, resulting in too low pH at the implantation site, which can easily induce an inflammatory response. At the same time, the inactive groups of the polymer make it lack osteogenic activity, which limits the further application of the aforementioned polymer materials in the field of bone defect repair.
[0005] Therefore, there is an urgent need to provide a new type of bone scaffold that can improve the defects of polymer bone scaffolds that produce acidic products during degradation and lack osteogenic activity. Summary of the invention
[0006] The object of the present invention is to provide a SrCO3 / polymer composite bone scaffold and a preparation method thereof, which can improve the defects of polymer material bone scaffold degradation to produce acidic products and lack of osteogenic activity.
[0007] In a first aspect, the present invention provides a SrCO3 / polymer composite bone scaffold, which is composited by SrCO3 microrods and polymer materials, wherein the polymer materials include at least one of polylactic acid, polyglycolic acid, polycaprolactone, polylactic acid-carboxylic acid copolymer or polydioxanone.
[0008] Optionally, based on the mass of the composite bone scaffold, in the SrCO3 / polymer composite bone scaffold, the mass fraction of the SrCO3 microrods is 0.5-4wt%, and the mass fraction of the polymer material is 96-99.5wt%.
[0009] Optionally, the SrCO3 microrod is composed of a plurality of SrCO3 particle units, the diameter of the SrCO3 particle unit is 0.1-0.5 μm, and the length is 0.8-1.5 μm. The plurality of SrCO3 particle units are arranged axially in parallel to form the main axis structure of the SrCO3 microrod, and another plurality of the SrCO3 particle units are arranged axially obliquely on the main axis structure to form a branch structure of the SrCO3 microrod, and there are more than one branch structures.
[0010] Optionally, the diameter of the main axis structure of the SrCO3 microrod is 0.5-3 μm, the length of the main axis structure is 6-15 μm, the diameter of the branch structure is 0.2-2 μm, and the length of the branch structure is 2-10 μm.
[0011] Optionally, the particle size of the polymer material is 0.1 to 100 μm.
[0012] Optionally, the SrCO3 / polymer composite bone scaffold is a porous structure, the porosity of the porous structure is 45-60%, and the pore size is 200-400 μm.
[0013] In a second aspect, the present invention provides a method for preparing the aforementioned SrCO3 / polymer composite bone scaffold, comprising the following steps:
[0014] (1) Preparation of SrCO3 microrods;
[0015] (2) mixing the SrCO3 microrods and polymer powder to prepare a mixed powder;
[0016] (3) The mixed powder is subjected to selective laser sintering to prepare a SrCO3 / polymer composite bone scaffold.
[0017] Optionally, step (1) specifically includes the following steps:
[0018] (1-1) dissolving strontium chloride hexahydrate in a mixed solvent of anhydrous ethanol and deionized water to obtain a mixed solution A;
[0019] (1-2) dissolving anhydrous sodium carbonate in a mixed solvent of anhydrous ethanol and deionized water to obtain a mixed solution B;
[0020] (1-3) Add citric acid to mixed solution A, and while the mixed solution A is constantly stirred, add mixed solution B dropwise into the mixed solution A, continue stirring and mixing, and obtain a white suspension. After centrifugation, washing, and drying, SrCO3 microrods are prepared.
[0021] Optionally, the mass volume ratio of strontium chloride hexahydrate, anhydrous ethanol and deionized water in mixed solution A is 0.2-0.3 g:120-180 mL:10-30 mL; the mass volume ratio of anhydrous sodium carbonate, anhydrous ethanol and deionized water in mixed solution B is 0.08-0.12 g:10-30 mL:10-30 mL; the mass volume ratio of citric acid added to mixed solution A to mixed solution A is 0.01-0.03 g:130-210 mL, the stirring speed is 500-1000 r / min, and the stirring and mixing time is continued for 20-40 hours.
[0022] Optionally, the process parameters of the selective laser sintering in step (3) are: laser power of 1 to 3 W, scanning speed of 200 to 300 mm / s, scanning spacing of 0.1 to 1.0 mm, spot diameter of 0.3 to 1.0 mm, and the powder thickness of the mixed powder is 0.05 to 0.1 mm.
[0023] In summary, the present invention has at least one of the following beneficial effects:
[0024] 1. The present invention provides a SrCO3 / polymer composite, in which SrCO3 and polymer materials are organically combined. The introduced SrCO3 is alkaline in hydrolysis and can neutralize the acidic products produced by the degradation of polymer materials in the bone scaffold to prevent inflammatory reactions at the implantation site. In addition, the Sr ions continuously released by the hydrolysis of SrCO3 can promote the differentiation of stem cells into osteoblasts and inhibit the production of osteoclasts, which effectively solves the problem that polymers do not have osteogenic activity.
[0025] 2. The present invention provides a SrCO3 / polymer composite bone scaffold, wherein SrCO3 has a specific morphological structure and size, and the SrCO3 microrod is composed of a plurality of SrCO3 microparticle units, wherein the plurality of SrCO3 microparticle units are arranged axially in parallel to form the main axis structure of the SrCO3 microrod, and the plurality of SrCO3 microparticle units are arranged axially obliquely to the main axis to form the branch structure of the SrCO3 microrod, wherein there are more than one branch structure, and the main axis structure and the branch structure are easily intertwined with each other, so that the SrCO3 microrod presents a three-dimensional network structure, which is organically combined with the polymer material, and is beneficial to better neutralize the acidic products and release the Sr ion active components along the three-dimensional network structure, thereby promoting cell proliferation and osteogenic differentiation.
[0026] 3. The present invention provides a method for preparing a SrCO3 / polymer composite bone scaffold. The present invention adopts a specific preparation process to selectively laser sinter SrCO3 microrods with a specific ratio and specific morphological structure size with a polymer material with a specific particle size. In addition to being able to be customized according to differentiated needs to meet actual usage needs to the greatest extent, the prepared bone scaffold has a suitable porosity and pore size, which is beneficial to its degradation after implantation, cell adhesion and the exchange of nutrients and metabolites, further improving the osteogenesis efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the SrCO3 powder prepared in Example 1;
[0028] Figure 2 This is a schematic diagram of a model for preparing a bone scaffold in Example 1;
[0029] Figure 3 The pH changes of 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, 4.0% SrCO3 / PLLA composite bone scaffold groups prepared in Examples 1-4 and the PLLA bone scaffold of Comparative Example 1 after degradation in PBS buffer for a specific period of time;
[0030] Figure 4 Cell counting (CCK-8) results of 3-day co-culture of 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, 4.0% SrCO3 / PLLA composite bone scaffold groups prepared in Examples 1-4 and PLLA, 1.0% SrCO3 / PLLA (100 μm), 1.0% SrCO3 / PLLA (500 μm) bone scaffolds prepared in Comparative Examples 1 to 3 with mouse bone marrow mesenchymal stem cells;
[0031] Figure 5 The alkaline phosphatase (ALP) staining results of the PLLA bone scaffold of comparative example 1 co-cultured with mBMSCs for 5 days;
[0032] Figure 6 The alkaline phosphatase (ALP) staining results of the 0.5% SrCO3 / PLLA composite bone scaffold prepared in Example 1 and co-cultured with mBMSCs for 5 days;
[0033] Figure 7 The alkaline phosphatase (ALP) staining results of the 1.0% SrCO3 / PLLA (100 μm) composite bone scaffold prepared in Comparative Example 2 and co-cultured with mBMSCs for 5 days;
[0034] Figure 8The alkaline phosphatase (ALP) staining results of the 1.0% SrCO3 / PLLA composite bone scaffold prepared in Example 2 and co-cultured with mBMSCs for 5 days;
[0035] Fig. 9 The alkaline phosphatase (ALP) staining results of the 1.0% SrCO3 / PLLA (500 μm) composite bone scaffold prepared in Comparative Example 3 and co-cultured with mBMSCs for 5 days;
[0036] Fig.10 The alkaline phosphatase (ALP) staining results of the 2.0% SrCO3 / PLLA composite bone scaffold prepared in Example 3 and co-cultured with mBMSCs for 5 days;
[0037] Fig.11 This is the alkaline phosphatase (ALP) staining result of the 4.0% SrCO3 / PLLA composite bone scaffold prepared in Example 4 co-cultured with mBMSCs for 5 days. DETAILED DESCRIPTION
[0038] The present invention provides a SrCO3 / polymer composite bone scaffold and a preparation method. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0039] At present, polymer materials such as poly(lactic acid), poly(glycolic acid), and polycaprolactone are often used to prepare bone scaffolds because of their high mechanical strength and stiffness, and their ability to mimic the load-bearing properties required for bone tissue regeneration. However, since polymer materials produce acidic products during their degradation in the body, the pH of the implantation site is too low, which can easily induce an inflammatory response. At the same time, the inactive groups of the polymers make them lack osteogenic activity, which limits the further application of the aforementioned polymer materials in the field of bone defect repair.
[0040] In order to enhance the osteogenic performance of polymers, researchers have made many efforts, such as adding growth factors such as BMP-2, VEGF, PDGF-BB, etc., but these growth factors are expensive, easy to lose activity, and safety and effective doses are difficult to guarantee. In addition, researchers also dope bioceramic materials with bioactive ions (such as Sr ions, Ca ions, Mg ions, etc.) that promote cell proliferation and osteogenic differentiation, but the content of dopants is generally limited, and it is difficult to show the best osteogenic effect. For this reason, the inventors surprisingly found after long-term research that by preparing SrCO3 / polymer composite bone scaffolds, SrCO3 hydrolysis is alkaline, which can neutralize the acidic products produced by the degradation of polymer materials in the bone scaffold to prevent inflammatory reactions from occurring at the implantation site, in addition, the Sr ions continuously released by SrCO3 hydrolysis can promote the differentiation of stem cells into osteoblasts, and inhibit the generation of osteoclasts, which well solves the problem that polymers do not have osteogenic activity. Furthermore, the prepared SrCO3 is a microrod with a specific morphology, structure and size. The SrCO3 microrod is composed of a plurality of SrCO3 particle units. The plurality of SrCO3 particle units are arranged axially in parallel to form the main axis structure of the SrCO3 microrod, and a plurality of SrCO3 particle units are arranged axially inclined to the main axis to form a branch structure of the SrCO3 microrod. There are more than one branch structure. The main axis structures and branch structures of the plurality of SrCO3 microrods are easily intertwined to form a three-dimensional network structure, which forms an organic bond with the polymer material, and is beneficial to better neutralize the acidic products and release the Sr ion active components along the three-dimensional network structure, thereby promoting cell proliferation and osteogenic differentiation. Furthermore, the present invention adopts a specific preparation process to selectively laser sinter SrCO3 microrods with a specific ratio and a specific morphology with a polymer material. In addition to being able to be customized according to differentiated needs in order to meet actual usage needs to the greatest extent, the prepared bone scaffold has a suitable porosity and pore size, which is beneficial to its degradation after implantation, cell adhesion, and the exchange of nutrients and metabolites, further improving the osteogenesis efficiency.
[0041] Specifically, the present invention provides a SrCO3 / polymer composite bone scaffold, which is composited by SrCO3 microrods and polymer materials, wherein the polymer material includes at least one of polylactic acid, polyglycolic acid, polycaprolactone, polylactic acid-carboxylic acid copolymer and polydioxanone.
[0042] In some embodiments of the invention, in the SrCO3 / polymer composite bone scaffold, based on the mass of the composite bone scaffold, the mass fraction of the SrCO3 microrods is 0.5-4wt%, and the mass fraction of the polymer material is 96-99.5wt%, preferably the mass fraction of the SrCO3 microrods is 1-2wt%; the mass fraction of the polymer material is 98-99wt%. Within this mass ratio range, the SrCO3 / polymer composite bone scaffold is beneficial to neutralize acidic products and release Sr ion active ingredients, thereby promoting cell proliferation and osteogenic differentiation.
[0043] In some embodiments of the invention, the particle size of the polymer material is 0.1 to 100 μm, preferably 1 to 80 μm, and more preferably 15 to 25 μm. Within this particle size range, it is beneficial to uniformly mix the polymer material and the SrCO3 micron rods, and subsequently prepare the SrCO3 / polymer composite bone scaffold through selective sintering, which has good supporting performance and osteogenesis performance.
[0044] In some embodiments of the invention, the SrCO3 microrod is composed of a plurality of SrCO3 microparticle units, the diameter of the SrCO3 microparticle unit is 0.1-0.5 μm, the length is 0.8-1.5 μm, the axial parallel arrangement of the plurality of SrCO3 microparticle units forms the main axis structure of the SrCO3 microrod, and the axial arrangement of the plurality of SrCO3 microparticle units is inclined to the main axis to form the branch structure of the SrCO3 microrod, and there are more than one branch structure. In some embodiments of the invention, the diameter of the main axis structure of the SrCO3 microrod is 0.5-3 μm, the length of the main axis structure is 6-15 μm, the diameter of the branch structure is 0.2-2 μm, and the length of the branch structure is 2-10 μm.
[0045] The SrCO3 microrods of specific morphology, structure and size and the polymer materials of specific size in the present invention can better form an organic combination. The main axis structure and the inclined multiple branch structures of the SrCO3 microrods are easily intertwined to form a three-dimensional network and distributed in the polymer materials, so that the introduced SrCO3 can better extend between the polymer materials, neutralize acidic products and release bioactive ions, thereby improving the osteogenic performance.
[0046] In some embodiments of the invention, the SrCO3 / polymer composite bone scaffold is a porous structure with a pore size of 200 to 400 μm and a porosity of 45 to 60%. A bone scaffold with a suitable porosity and pore size is conducive to its degradation after implantation, cell adhesion, and the exchange of nutrients and metabolites, further improving the osteogenesis efficiency.
[0047] The present invention provides a method for preparing a SrCO3 / polymer composite bone scaffold, comprising the following preparation steps:
[0048] (1) Preparation of SrCO3 microrods;
[0049] (2) mixing the SrCO3 microrods and polymer powder to prepare a mixed powder;
[0050] (3) The mixed powder is subjected to selective laser sintering to prepare a SrCO3 / polymer composite bone scaffold.
[0051] In some embodiments of the present invention, step (1) specifically includes the following steps:
[0052] (1-1) dissolving strontium chloride hexahydrate in a mixed solvent of ethanol and deionized water to obtain a mixed solution A;
[0053] (1-2) dissolving anhydrous sodium carbonate in a mixed solvent of ethanol and deionized water to obtain a mixed solution B;
[0054] (1-3) Add citric acid to mixed solution A, and while the mixed solution A is constantly stirred, add mixed solution B dropwise into solution A, and continue stirring to obtain a white suspension. After centrifugation, washing, and drying, SrCO3 microrods are prepared.
[0055] In some embodiments of the present invention, the mass volume ratio of strontium chloride hexahydrate, ethanol and deionized water in mixed solution A is 0.2-0.3 g:120-180 mL:10-30 mL; the mass volume ratio of anhydrous sodium carbonate, ethanol and deionized water in mixed solution B is 0.08-0.12 g:10-30 mL:10-30 mL; the mass volume ratio of citric acid added to mixed solution A to mixed solution A is 0.01-0.03 g:130-210 mL, the stirring speed is 500-1000 r / min, and the stirring and mixing time is continued for 20-40 h.
[0056] In some embodiments of the present invention, the process parameters of the selective laser sintering in step (3) are: laser power of 1 to 3 W, scanning speed of 200 to 300 mm / s, scanning spacing of 0.1 to 1.0 mm, spot diameter of 0.3 to 1.0 mm, and the powder thickness of the mixed powder is 0.05 to 0.1 mm.
[0057] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0058] In the following examples, the raw materials used are all commercially available.
[0059] Example 1
[0060] This embodiment provides a method for preparing a SrCO3 / polymer composite bone scaffold, comprising the following steps:
[0061] (1) Preparation of SrCO3 microrods:
[0062] (1-1) SrCl2·6H2O (analytical grade) was dissolved in a mixed solvent of anhydrous ethanol and deionized water to obtain a mixed solution A, wherein the mass volume ratio of strontium chloride hexahydrate, anhydrous ethanol and deionized water was 0.267 g:160 mL:20 mL;
[0063] (1-2) dissolving anhydrous sodium carbonate (Na2CO3, analytical grade) in a mixed solvent of anhydrous ethanol and deionized water to obtain a mixed solution B; wherein the mass volume ratio of anhydrous sodium carbonate, anhydrous ethanol and deionized water is 0.106 g:20 mL:20 mL;
[0064] (1-3) 0.026 g of citric acid was added to the mixed solution A, and the mixed solution A was continuously stirred at a stirring speed of 500 r / min. The mixed solution B was added dropwise to the mixed solution A at a speed of 1.5 mL per minute. After the addition was completed, the stirring and mixing were continued at the same speed to obtain a white suspension. The suspension was centrifuged and washed with deionized water, which was repeated three times and dried to obtain SrCO3 powder.
[0065] Figure 1 This is a scanning electron microscope image of the SrCO3 powder prepared in Example 1. Figure 1 It can be seen that the SrCO3 powder is SrCO3 microrods, which are composed of multiple SrCO3 particle units. The diameter of the SrCO3 particle unit is 0.1-0.5μm, and the length is 0.8-1.5μm. The axial parallel arrangement of multiple SrCO3 particle units forms the main axis structure of the SrCO3 microrod, and there are multiple SrCO3 particle units arranged axially inclined to the main axis to form the branch structure of the SrCO3 microrod. There are 2-4 branch structures. The diameter of the main axis structure of the SrCO3 microrod is 0.5-3μm, the length of the main axis structure is 6-15μm, the diameter of the branch structure is 0.2-2μm, and the length of the branch structure is 2-10μm.
[0066] (2) SrCO3 microrods and polymer powder are mixed to prepare a mixed powder. The polymer powder in this embodiment is poly(lactic acid) powder (PLLA, weight average molecular weight M wThe particle size is 150,000, and the particle size is 15-25μm, Polymtek). Based on the mass of the mixed powder, the mass fraction of SrCO3 microrods in the mixed powder is 0.5wt%, and the mass fraction of PLLA is 99.5wt%. The SrCO3 microrods and PLLA are placed in a grinding mortar and lightly ground for 20 minutes to fully mix the powders to obtain a uniformly mixed mixed powder.
[0067] (3) The mixed powder was subjected to selective laser sintering, and a bone scaffold model with a size of Φ6 mm × 1.5 mm, a pore size of 300 μm, and a porosity of 50% (porosity = (pore volume / total volume) × 100%) was designed using Autodesk Inventor 3D modeling software, as shown in FIG. Figure 2 As shown, the bone scaffold model is saved in .stl format, and the bone scaffold model is imported into the control software 3DPrinter of the selective laser sintering system, and the printing parameters are set: spot diameter 300μm, laser power 1.2W, scanning speed 300mm / s, powder thickness 0.05mm, scanning spacing 0.3mm, and the mixed powder is placed in the powder cylinder of the selective laser sintering system. The powder spraying device of the selective laser sintering system first spreads a layer of mixed powder, preheats to a melting point close to the mixed powder, and then uses laser irradiation to scan the cross-sectional shape of the model to be formed, so that the mixed powder is melted and the sintered parts are bonded together. This powder spreading and sintering process is repeated, and after sintering layer by layer, a 0.5% SrCO3 / PLLA composite bone scaffold is obtained.
[0068] Example 2
[0069] The difference between Example 2 and Example 1 is that the mass fraction of SrCO3 microrods in the mixed powder in step (2) of Example 2 is 1.0wt%, the mass fraction of PLLA is 99.0wt%, and the remaining preparation steps are the same as those in Example 1.
[0070] Example 3
[0071] The difference between Example 3 and Example 1 is that the mass fraction of SrCO3 microrods in the mixed powder in step (2) of Example 3 is 2.0wt%, the mass fraction of PLLA is 98.0wt%, and the remaining preparation steps are the same as those in Example 1.
[0072] Example 4
[0073] The difference between Example 4 and Example 1 is that the mass fraction of SrCO3 microrods in the mixed powder in step (2) of Example 4 is 4.0wt%, the mass fraction of PLLA is 96.0wt%, and the remaining preparation steps are the same as those in Example 1.
[0074] Comparative Example 1
[0075] The difference between Comparative Example 1 and Example 1 is that a method for preparing a PLLA bone scaffold is provided, steps (1) and (2) are omitted, and step (3) which is the same as that of Example 1 is adopted to selectively laser sinter the PLLA powder to prepare the PLLA bone scaffold.
[0076] Comparative Example 2
[0077] The difference between Comparative Example 2 and Example 2 is that the pore size of the bone scaffold model prepared in step (3) of Comparative Example 2 is 100 μm, and the remaining preparation steps are the same as those of Example 2.
[0078] Comparative Example 3
[0079] The difference between Comparative Example 3 and Example 2 is that the pore size of the bone scaffold model prepared in step (3) of Comparative Example 3 is 500 μm, and the remaining preparation steps are the same as those of Example 2.
[0080] Performance Testing:
[0081] 1. PBS buffer immersion experiment:
[0082] The 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, 4.0% SrCO3 / PLLA composite bone scaffold groups prepared in Examples 1 to 4 and the PLLA bone scaffold prepared in Comparative Example 1 were immersed in PBS buffer at a volume weight ratio of 20 mL / g and kept in an oscillator at 37°C for 1, 4, 7, 14, 21 and 28 days, and the pH value of the immersion solution was measured with a pH meter. The results are shown in FIG. Figure 3As shown, the pH values of the SrCO3 / PLLA composite bone scaffold groups of Examples 1 to 4 during degradation are higher than those of the pure PLLA bone scaffold group. After 28 days of degradation, the pH value of Comparative Example 1 is 6.78, and the pH values of the 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, and 4.0% SrCO3 / PLLA composite bone scaffold groups are 6.94, 7.01, 7.20, and 7.10, respectively. It can be seen that the SrCO3 in the SrCO3 / PLLA composite bone scaffold neutralizes the polylactic acid produced by the degradation of PLLA, and in Examples 2-4, when the mass fraction of SrCO3 is 1.0 to 4.0wt%, the acid neutralization effect is better. As the mass fraction of SrCO3 in the SrCO3 / PLLA composite bone scaffold increases, the acid neutralization effect of SrCO3 increases, and the rate of pH decrease is significantly lower than that of the PLLA bone scaffold. When the mass fraction of SrCO3 reaches 2.0wt%, the best effect is achieved. However, as the mass fraction of SrCO3 continues to increase, the rate of pH decrease increases. The main reason for this is that excessive SrCO3 promotes the degradation of PLLA, which increases the degradation rate of PLLA and leads to a significant decrease in pH.
[0083] 2. Biocompatibility test:
[0084] Biocompatibility experiments were carried out using the 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, and 4.0% SrCO3 / PLLA composite bone scaffold groups obtained in Examples 1 to 4 and the PLLA, 1.0% SrCO3 / PLLA (100 μm), and 1.0% SrCO3 / PLLA (500 μm) bone scaffolds prepared in Comparative Examples 1 to 3, respectively. The cells selected were mouse bone marrow mesenchymal stem cells (mBMSCs).
[0085] First, the 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, 4.0% SrCO3 / PLLA composite bone scaffold groups of Examples 1 to 4 and the PLLA, 1.0% SrCO3 / PLLA (100 μm), and 1.0% SrCO3 / PLLA (500 μm) bone scaffolds prepared in Comparative Examples 1 to 3 were soaked in 70% alcohol for 3 hours and then sterilized by ultraviolet light irradiation. Subsequently, the bone scaffolds were placed in a 48-well plate and mBMSCs were inoculated in the wells where the bone scaffolds were placed at a density of 5,000 cells per well. After 3 days (the culture medium was a high-glucose culture medium containing 10% fetal bovine serum), a cell technology reagent (CCK-8) was added and the absorbance was measured at 450 nm.
[0086] Test results such as Figure 4As shown in the figure, the OD values of PLLA, 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA (100 μm), 1.0% SrCO3 / PLLA, 1.0% SrCO3 / PLLA (500 μm), 2.0% SrCO3 / PLLA and 4.0% SrCO3 / PLLA bone scaffolds are 0.521, 0.706, 0.676, 0.750, 0.685, 0.704 and 0.521, respectively. It can be seen that all five groups of scaffolds have good biocompatibility, and the SrCO3 in Examples 2-3 has good biocompatibility. In the / PLLA composite bone scaffold group, when the mass fraction of SrCO3 is 1.0-2.0wt%, it has a significant effect on promoting the proliferation of mBMSCs compared with the PLLA bone scaffold in Comparative Example 1, among which 1.0% SrCO3 / PLLA composite bone scaffold has the best promoting effect. This is because Sr ions can promote cell proliferation, but when Sr ions are excessive, they will also show a certain inhibitory effect on cell proliferation. The amount of Sr ions released by the 1.0% SrCO3 / PLLA composite bone scaffold during bone repair can achieve the best effect of promoting cell proliferation. However, compared with Example 2, in Comparative Examples 2 and 3, when the pore size of the 1.0% SrCO3 / PLLA scaffold is 100 μm and 500 μm, the effect of the scaffold in promoting cell proliferation is significantly reduced. This is because when the pore size of the scaffold is small, cells cannot grow into the scaffold, and when the pore size of the scaffold is too large, it is not conducive to cell adhesion. This is why the OD values of the 1.0% SrCO3 / PLLA (100 μm) and 1.0% SrCO3 / PLLA (500 μm) scaffold groups are significantly lower than those of the 1.0% SrCO3 / PLLA scaffold group, and the effect on cell proliferation is significantly reduced.
[0087] 3. Alkaline phosphatase (ALP) staining experiment:
[0088] The sterilized 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA, 2.0% SrCO3 / PLLA, 4.0% SrCO3 / PLLA composite bone scaffold groups of Examples 1 to 4 and the PLLA bone scaffold of Comparative Example 1 were placed in a 48-well plate and inoculated with mBMSCs at a density of 10,000 cells per well. Fresh culture medium containing osteogenic induction solution was replaced every two days. After culturing for 5 days, the culture medium was aspirated and the cells were fixed with 4% paraformaldehyde and then stained with ALP stain. The staining results are shown in FIG. Figures 5 to 11 As shown, through Figure 5 , 6, 8, 10 and 11, it can be seen that the ALP expression levels of the 0.5% SrCO3 / PLLA, 1.0% SrCO3 / PLLA and 2.0% SrCO3 / PLLA composite bone scaffold groups are significantly higher than those of the PLLA bone scaffold, and the ALP expression level of the 1.0% SrCO3 / PLLA scaffold group is the highest, proving that it has the best osteogenic performance. Sr ions can promote the differentiation of stem cells into osteoblasts very well, but the higher the solubility of Sr ions, the more significant the effect of promoting the osteogenic differentiation of stem cells. However, when the proportion of SrCO3 in the PLLA scaffold is 1%, the released Sr ions can achieve the best effect of promoting the osteogenic differentiation of stem cells, that is, the 1.0% SrCO3 / PLLA scaffold has the best osteogenic performance. However, the pore size of the scaffold is also very important for the osteogenic performance. Figure 7-9 It can be seen that the ALP expression levels in the 1.0% SrCO3 / PLLA (100 μm) and 1.0% SrCO3 / PLLA (500 μm) composite bone scaffold groups were significantly lower than those in the 1.0% SrCO3 / PLLA scaffold group. When the pore size of the scaffold is too small, stem cells cannot grow into the scaffold; and when the pore size of the scaffold is too large, it is not conducive to the adhesion of stem cells, which will lead to a significant decrease in the osteogenic performance of the scaffold.
[0089] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A SrCO3 / polymer composite bone scaffold, characterized in that: The bone scaffold is composited by SrCO3 microrods and polymer materials, wherein the polymer materials include at least one of polylactic acid, polyglycolic acid, polycaprolactone, polylactic acid-carboxylic acid copolymer or polydioxanone; The SrCO3 microrod is composed of a plurality of SrCO3 microparticle units, the diameter of the SrCO3 microparticle unit is 0.1-0.5 μm, the length is 0.8-1.5 μm, the plurality of SrCO3 microparticle units are arranged axially in parallel to form a main axis structure of the SrCO3 microrod, and a plurality of the SrCO3 microparticle units are arranged axially obliquely on the main axis structure to form a branch structure of the SrCO3 microrod, and there are more than one branch structure; the diameter of the main axis structure of the SrCO3 microrod is 0.5-3 μm, the length of the main axis structure is 6-15 μm, the diameter of the branch structure is 0.2-2 μm, and the length of the branch structure is 2-10 μm; Based on the mass of the composite bone scaffold, in the SrCO3 / polymer composite bone scaffold, the mass fraction of the SrCO3 microrods is 0.5-4wt%, and the mass fraction of the polymer material is 96-99.5wt%; The particle size of the polymer material is 0.1-100 μm; The SrCO3 / polymer composite bone scaffold is a porous structure with a porosity of 45-60% and a pore size of 200-400 μm.
2. A method for preparing the SrCO3 / polymer composite bone scaffold according to claim 1, characterized in that: The method comprises the following preparation steps: (1) Preparation of SrCO3 microrods; (2) mixing the SrCO3 microrods and polymer powder to prepare a mixed powder; (3) The mixed powder is subjected to selective laser sintering to prepare a SrCO3 / polymer composite bone scaffold.
3. The method for preparing the SrCO3 / polymer composite bone scaffold according to claim 2, characterized in that: Step (1) specifically includes the following steps: (1-1) dissolving strontium chloride hexahydrate in a mixed solvent of ethanol and deionized water to obtain a mixed solution A; (1-2) dissolving anhydrous sodium carbonate in a mixed solvent of ethanol and deionized water to obtain a mixed solution B; (1-3) Add citric acid to mixed solution A, and while the mixed solution A is constantly stirred, add mixed solution B dropwise into the mixed solution A, continue stirring and mixing, and obtain a white suspension. After centrifugation, washing, and drying, SrCO3 microrods are prepared.
4. The method for preparing the SrCO3 / polymer composite bone scaffold according to claim 3, characterized in that: The mass volume ratio of strontium chloride hexahydrate, anhydrous ethanol and deionized water in mixed solution A is 0.2~0.3g:120~180mL:10~30mL; the mass volume ratio of anhydrous sodium carbonate, anhydrous ethanol and deionized water in mixed solution B is 0.08~0.12g:10~30mL:10~30mL; the mass volume ratio of citric acid added to mixed solution A to mixed solution A is 0.01~0.03g:130~210mL, the stirring speed is 500~1000r / min, and the stirring and mixing time is continued for 20~40h.
5. The method for preparing the SrCO3 / polymer composite bone scaffold according to claim 2, characterized in that: The process parameters of the selective laser sintering in step (3) are: laser power of 1-3 W, scanning speed of 200-300 mm / s, scanning spacing of 0.1-1.0 mm, spot diameter of 0.3-1.0 mm, and the powder thickness of the mixed powder is 0.05-0.1 mm.
Citation Information
Patent Citations
Strontium carbonate-modified silk fibroin composite material and preparation method thereof
CN106730020A
Poly-L-lactic acid (PLLA) / ZIF-8 composite bone scaffold and preparation method thereof
CN110538350A